Ellagic acid ameliorates cisplatin-induced acute kidney injury by regulating inflammation and SIRT6/TNF-α signaling - Yuqi Gao; Kezheng Peng; Yida Wang; Yannan Guo; Chenye Zeng; Rui Hua; Qingfei Liu; Xue Li; Ying Qiu; Zhao Wang (Food Science and Human Wellness)
Despite cisplatin has been widely used in the treatment of various cancers, the noteworthy nephrotoxicity greatly constrained its clinical value. For this reason, finding novel targeted therapies to attenuate the nephrotoxicity of cisplatin should be pretty significant. Our previous study found that histone deacetylase sirtuin 6 (SIRT6) could be an ideal target for the treatment of cisplatin-induced acute kidney injury. In this study, we explored the protective effects of ellagic acid, a natural polyphenol compound that activates SIRT6, on cisplatin-induced nephrotoxicity. Pre-treatment of ellagic acid attenuated cytotoxicity of cisplatin in primary renal cells and TCMK-1 cells. Moreover, ellagic acid ameliorated renal dysfunction, apoptosis and fibrosis induced by cisplatin in mice. Furthermore, ellagic acid reduced nephrotoxicity-associated inflammatory factor interleukin (IL)-1β and IL-6 expression both in vitro and in vivo. Mechanistically, ellagic acid reversed cisplatin-reduced SIRT6 expression and diminished cisplatin-induced tumor necrosis factor (TNF)-α expression. And SIRT6 knockdown abrogated the protective effects of ellagic acid on cisplatin-induced cell apoptosis, indicating the renal-protective effects of ellagic acid are mainly dependent on ellagic acid-mediated SIRT6 activation. Our results provide preclinical rationale for using ellagic acid as a feasible and promising agent to ameliorate cisplatin-induced acute kidney injury, and support ellagic acid as a potential adjunctive therapy for future cancer treatment.